2004
DOI: 10.1007/s00432-003-0539-2
|View full text |Cite
|
Sign up to set email alerts
|

Photodynamic therapy of virus-associated epithelial tumours of the face in organ transplant recipients

Abstract: ALA-PDT is a valuable therapeutic alternative for the treatment of multifocal skin tumours in organ-transplanted patients. Furthermore, we see a growing role of ALA-PDT also for patients with frequently relapsing tumours of the skin with known genetically determined tumourigenesis (Gorlin-Goltz syndrome).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 33 publications
1
14
0
Order By: Relevance
“…A recent short report found that MAL-PDT for NBCCS improves patient satisfaction and reduces the need for surgical procedures [130]. Topical PDT has been used to treat BCC in immunosuppressed patients with ALA-PDT clearing 30/32 facial tumours (including 21 BCC) in 5 OTR after one to three treatments [131]. PDT has also been assessed for its ability to prevent/delay new cancer development in OTR.…”
Section: Photodynamic Therapymentioning
confidence: 99%
“…A recent short report found that MAL-PDT for NBCCS improves patient satisfaction and reduces the need for surgical procedures [130]. Topical PDT has been used to treat BCC in immunosuppressed patients with ALA-PDT clearing 30/32 facial tumours (including 21 BCC) in 5 OTR after one to three treatments [131]. PDT has also been assessed for its ability to prevent/delay new cancer development in OTR.…”
Section: Photodynamic Therapymentioning
confidence: 99%
“…In a randomized controlled trial, the same group reported an observed clearance of AK in 13 out of 17 OTRs at 16 weeks in areas treated by MAL-PDT (3 h; 600–730 nm; 75 J/cm 2 ; 80 mW/cm 2 ) [87]. Another group reported complete remission of 24 tumors (75%) in five OTRs with 32 facial tumors (21 BCC, eight AK, one keratoacanthoma and two SCC) following PDT (ALA: 3–5 h; 635 nm; 120 J/cm 2 ; 100 mW/cm 2 ) [88]. Two tumors, both SCC, were refractory to PDT.…”
Section: Clinical Applications Of Pdt For Cutaneous Neoplasiamentioning
confidence: 99%
“…Although the number of reported studies so far is small, PDT in OTRs appears to be more effective for BCC than AK with remission rates of 75% after 12 weeks, compared to 48% in AK [60], and a low recurrence rate of under 6% after 22 months of followup [43, 61]. …”
Section: Photodynamic Therapymentioning
confidence: 99%